Magnetoresistance oscillations up to 32 K in the organic metal β″-(ET)₄(H₃O)[Fe(C₂O₄)₃]⋅C₆H₄Cl₂ - Laukhin, V.N.; Audouard, A.; Vignolles, D.; Canadell, E.; Prokhorova, T.G.; Yagubskii, E.B. (Физика низких температур, 2011)
Magnetic torque and magnetoresistance of the quasi-two-dimensional charge transfer salt β″-(ET)₄(H₃O)[Fe(C₂O₄)₃]⋅C₆H₄Cl₂ have been investigated in pulsed magnetic fields of up to 55 T. At variance with de Haas–van Alphen oscillations, Shubnikov–de Haas oscillations are observed up to temperatures as high as 32 K at ambient pressure despite a significant thermal damping in the low-temperature range. This feature, observed under applied pressure as well, is interpreted on the basis of the coexistence of a closed orbit and a quantum interference path with the same cross section.